Physicochemical properties and cytocompatibility assessment of non-degradable scaffolds for bone tissue engineering applications - Pereira, H. (2020)
Bone is a dynamic tissue with an amazing but yet limited capacity of self-healing. Bone is the second most transplanted tissue in the world and there is a huge need for bone grafts and substitutes which lead to a decrease in bone banks donors. In this study, we developed three-dimensional scaffolds based on Ti6Al4V, ZrO2 and PEEK targeting bone tissue engineering applications. Experimental mechanical compressive tests and finite element analyses were carried out to study the mechanical performance of the scaffolds. Overall, the scaffolds presented different hydrophilicity properties and a reduced elastic modulus when compared with the corresponding solid materials which can in some extension minimize the phenomenon of stress shielding. The ability as a scaffold material for bone tissue regeneration applications was evaluated in vitro by seeding human osteosarcoma (SaOS-2) cells onto the scaffolds. Then, the successful culture of SaOS-2 cells on developed scaffolds was monitored by assessment of cell's viability, proliferation and alkaline phosphatase (ALP) activity up to 14 days of culturing. The in vitro results revealed that Ti6Al4V, ZrO2 and PEEK scaffolds were cytocompatible allowing the successful culture of an osteoblastic cell line, suggesting their potential application in bone tissue engineering.